2008
DOI: 10.1016/j.pupt.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled ethanol potentiates the cough response to capsaicin in patients with airway sensory hyperreactivity

Abstract: To cite this version:Eva Millqvist, Ewa Ternesten-Hasséus, Mats Bende. Inhaled ethanol potentiates the cough response to capsaicin in patients with airway sensory hyperreactivity. Pulmonary Pharmacology & Therapeutics, 2008, 21 (5) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…FEV 1 was measured before and after each provocation. In accordance with dose-response relationships seen in several earlier studies using the same capsaicin provocation model (18,19,31,32), the missing data for those patients whose provocations were halted due to excess coughing were filled in by doubling the number of coughs evoked by 2.0 µmol/L capsaicin to represent the cough response to 10.0 µmol/L capsaicin.…”
Section: Capsaicin Provocationsupporting
confidence: 68%
See 2 more Smart Citations
“…FEV 1 was measured before and after each provocation. In accordance with dose-response relationships seen in several earlier studies using the same capsaicin provocation model (18,19,31,32), the missing data for those patients whose provocations were halted due to excess coughing were filled in by doubling the number of coughs evoked by 2.0 µmol/L capsaicin to represent the cough response to 10.0 µmol/L capsaicin.…”
Section: Capsaicin Provocationsupporting
confidence: 68%
“…This prospective study included 18 consecutively chosen patients, 9 women and 9 men, aged between 18 and 60 years, with a median age of 35 years (95% confidence interval [CI]: [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, the same group showed similar differences for SAR subjects when challenged with chlorine (Shusterman et al 2003). Patients with sensory hyperreactivity (Millqvist et al 2008) showed not only a higher number of coughs when provoked with 0.4 or 2 µM of capsaicin aerosols, their response was dose-dependent and increased by pre-inhalation of ethanol (5 and 25 %). Control subjects showed no response to ethanol inhalation.…”
Section: Discussionmentioning
confidence: 99%
“…Women with chronic cough show a heightened reflex compared to men, probably due to overexpression of TRPs (59). The exposition both to irritants and common intense odors seem to increase the cough reflex through the afferent pathway activated by TRPs (60,61). As discussed above, cough hypersensitivity is associated to the most common causes of chronic cough and it helps to understand the pathogenesis of the symptom.…”
Section: Shortness Of Breath 2014; 3 (4): 159-164mentioning
confidence: 96%